Availability and readiness of health facilities in Burkina Faso to provide antenatal care: trend analysis from 2012 to 2020 - Marie-Jeanne Offosse; Kadari Cissé; Désiré Somda; Anna Gage; Annie Haakenstad; Aduragbemi Banke-Thomas (Reproductive Health)
Abstract Background Antenatal care (ANC) is a critical maternal health service that, if well done, helps to reduce morbidity and mortality that could occur amongst pregnant women and their babies. This study analyses the trend in availability of and health facility readiness to provide high-quality ANC in Burkina Faso between 2012 and 2020, a period spanning the introduction of user-fee exemption policy and conflict in several regions. Methods We conducted a trend analysis of repeated cross-sectional health facility data using the nationally representative Service Availability and Readiness Assessment (SARA) surveys conducted in 2012, 2014, 2016 and 2018 and the census-based 2020 Health Harmonized Facilities Assessment (HHFA). We used tracer indicators defined by both surveys to characterize availability of services and health facility readiness. Availability and readiness indices were calculated using the equal-weighted approach, and the domain-weighted approach was used for readiness only. Trends were assessed using weighted multivariate linear regression. Results The number of health facilities surveyed was 686 in 2012, 766 in 2014, 677 in 2016, 794 in 2018 and 2,728 in 2020. ANC availability decreased from 72.2% in 2012 to 70.9% by 2020 in a statistically significant decreasing trend ( $$\:β\:=-0.011;\text{p}=0.001)$$ . For health facilities in rural locations, there was a statistically significant improvement in the ANC availability ( $$\:β\:=0.005;p=0.012),$$ while for those in urban settings, there was an overall statistically significant decreasing trend ( $$\:β\:=-0.013;p=0.004)$$ . For ANC service readiness, there was also a statistically significant decline after adjustments for health facility characteristics ( $$\:β\:=-0.203;p=0.003$$ ). Adjusted readiness score for staff and guidelines significantly decreased during the study period ( $$\:β\:=-3.491;p<0.001)$$ , while the adjusted score of other domains (equipment ( $$\:β\:=0.793;p<0.001)$$ , diagnosis ( $$\:β\:=0.618;p<0.001)$$ , and medicines ( $$\:β\:=1.26;p<0.001)$$ significantly increased. For both outcomes, there were regional disparities with Est showing statistically significant incremental changes and Centre Sud showing statistically significant declining trends. Conclusion This study shows decreases in ANC service availability and readiness between 2012 and 2020 in Burkina Faso. In the context of the implementation of global recommendations regarding ANC services and ongoing conflict in the country disrupting the health system, there is an urgent need to pay attention to ANC service strengthening, particularly the availability of trained health personnel and guidelines at all levels of the healthcare system, especially public health facilities in urban settings.